The Effects of Fermented Buffalo Milk (Dadih) Fortified with Red Dragon Fruit and Selenium on Adiponectin and Tumor Necrosis Factor-Alpha Levels in Obese Rats - Wulandari, Fitri; Rustanti, Ninik; Pramono, Adriyan (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
The increasing prevalence of obesity and its associated complications necessitates the exploration of functional foods as therapeutic interventions. This study aimed to analyze the effects of fermented buffalo milk (dadih) fortified with red dragon fruit (Hylocereus polyrhizus) and selenium on adiponectin and Tumor Necrosis Factor-Alpha (TNF-α) levels in obese rats. This experimental study employed a pretest-posttest control group design involving 20 Wistar rats divided into four groups: K1 (healthy control), K2 (obese control), P1, and P2 (obese intervention). K2, P1, and P2 were in obesity conditions induced by a high-fat-fructose diet (HFFD) for 28 days, and K1 was a healthy control group. Furthermore, dadih only and dadih fortified with red dragon fruit and selenium at 1.8 g/200 g body weight/day were administered to P1 and P2 groups, respectively. Treatment using dadih fortified with red dragon fruit and selenium significantly reduced weight gain (p=0.000) compared to K2 and P1. In addition, the P2 group showed increased adiponectin levels and decreased TNF-α levels (p=0.000) compared to the K2 and P1 groups. A strong negative correlation was found between adiponectin levels and TNF-alpha and body weight, while TNF-alpha and body weight showed a strong positive correlation. To conclude, fortifying dadih with red dragon fruit and selenium is more effective in improving the metabolic condition of obese rats compared to non-fortified dadih. This fortification significantly enhances adiponectin levels and reduces TNF-alpha levels. These findings suggest that functional food fortification could be a promising approach for managing obesity-related inflammation and metabolic disorders in humans, highlighting the potential application of dadih in dietary interventions.